1990
DOI: 10.1002/nur.4770130505
|View full text |Cite
|
Sign up to set email alerts
|

Factors that contribute to pressure sores in surgical patients

Abstract: In this prospective study examination was made of whether (a) time on the operating table, (b) proportion of intraoperative diastolic hypotensive episodes, (c) age, (d) preoperative serum albumin, (e) preoperative total protein levels, and (f) preoperative Braden scores could identify those patients who do and do not develop pressure sores during elective surgery. The stratified sample consisted of 125 adult patients. Fifteen patients (12%) developed a total of 23 pressure sores. A discriminant function using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
2
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 24 publications
7
87
2
6
Order By: Relevance
“…This finding has been reported by other investigators, 22,30 although other research 28,33,34 has indicated a relationship between age and pressure ulcers. Stordeur et al 30 found that mean ages were 64 years (SD, 11.5) in patients who did not acquire a pressure ulcer and 67.1 years (SD, 10.7) in patients who did acquire an ulcer (P = .06).…”
Section: Multivariate Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…This finding has been reported by other investigators, 22,30 although other research 28,33,34 has indicated a relationship between age and pressure ulcers. Stordeur et al 30 found that mean ages were 64 years (SD, 11.5) in patients who did not acquire a pressure ulcer and 67.1 years (SD, 10.7) in patients who did acquire an ulcer (P = .06).…”
Section: Multivariate Analysissupporting
confidence: 89%
“…11 Lindgren et al 21 found that 14.3% of surgical patients acquired a pressure ulcer during the time from surgery to 12 weeks after surgery, confirming the results of other studies. [22][23][24] Specifically, Schoonhoven et al 24 found that total operating room time was significantly associated with the occurrence of pressure ulcers. For every 30 minutes the surgery went beyond 4 hours, the risk for a pressure ulcer increased by approximately 33%.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto ao item idade, Kemp et al (1990), ao estudarem os fatores de risco para desenvolvimento de UP em pacientes cirúrgicos, encontraram uma média de 61 anos para os pacientes com risco de desenvolver UP. Langemo et al (1990); Braden e Bergstron (1994), Paranhos e Santos (1999) não encontraram diferenças estatísticas significantes referentes à idade nos pacientes com UP.…”
Section: Resultsunclassified
“…En la literatura es posible encontrar diversas investigaciones realizadas sobre los factores que contribuyen a la aparición de UPP en los pacientes quirúrgicos. Los estudios realizados han propuesto como factores que aumentan el riesgo: el tiempo que permanece el paciente en la mesa quirúrgica, la circulación extracorpórea y la edad (11,12); la edad, la pérdida de peso, las cifras de albúmina, el sexo femenino, la ingesta de alimentos, la puntuación de riesgo quirúrgico ASA (American Society of Anesthesiologists) y la puntuación cardiovascular NYHA (New York Heart Association) (10); los episodios de hipotensión, la temperatura del paciente durante la intervención y la reducción de la movilidad postoperatoria (13); y la duración de la intervención quirúrgica (14). Sin embargo, no hay acuerdo entre los diversos autores y los resultados son, hasta la fecha, contradictorios.…”
Section: Introductionunclassified